Scope of Laparoscopic Cholecystectomy in Patients with Previous Upper Abdominal Surgery (Anwer Khan Modern Medical College Journal, 2023)
Background: Laparoscopic cholecystectomy has become the treatment of choice for symptomatic gallstones. Previous upper abdominal surgery has been reported as a relative contraindication to laparoscopic cholecystectomy.This study specifically examined the effect of previous upper abdominal surgery on the feasibility and safety of laparoscopic cholecystectomy.Methods: A number of 50 patients of adult age group (25 to 60 years) who were admitted suffering from gall bladder pathology and having history of previous upper abdominal surgery in the surgery units of a tertiary level hospitalwithin the time period of September, 2013 to August, 2014 were included in this prospective observational study. With the consent of the patients, laparoscopic cholecystectomy was chosen as the surgical procedure. All these data were analyzed to find out the feasibility and safety of laparoscopic cholecystectomy in the patients with previous upper abdominal surgery.Results: The patients were classified into 3 groups: group 1, patients with no adhesions, group 2, patients with minimum adhesions and group 3, patients with moderate dense adhesions. The 3 groups were similar with respect to age and sex (P>0.05). Conversion to laparotomy was required in 5 (10%) patients (1 in group 1, 2 in group 2, and 3 in group 3). No statically significant difference was noted among groups with respect to the conversion rate (P>0.05). No per-operative complications occurred in any of the groups. The post-operative complication rates among groups were not statistically different (P>0.05).Conclusion: Previous upper abdominal surgery is not a contraindication to safe laparoscopic cholecystectomy. However, previous upper abdominal surgery is associated with an increased need for adhesiolysis, a chance for open conversion and a prolonged operation time.AKMMC J 2021; 12(1) : 11-15